ANALISIS HUKUM PADA TINDAK PIDANA PENGHINAAN SECARA MEDIA ONLINE - Laka Dodo Laia; Dikir Dakhi; Fariaman Laia (LPPM Universitas Nias Raya, 2026)
Electronic defamation is the act of attacking a person's honor or reputation through electronic media (the internet/social media). This action includes accusations of slander, defamation, and public insults. This research uses a normative legal research method with a conceptual approach and statutory regulations. The purpose of this research is a legal analysis of the crime of defamation in online media. Based on the research findings and discussion, freedom of expression is a right of every citizen and is protected by the state as long as it does not conflict with the Information and Electronic Transactions Law (UU ITE). The offense of defamation is not merely a general crime but also a complaint-based offense. A complaint-based offense is an offense that can only be prosecuted if filed by a person who feels aggrieved or has been a victim.